Miscommunication in the organization miscommunication in organizational communication and management : the organizational communication climate case of Equitable-PCI Trust Banking - Cancio, Rodolfo R.
This research focused on organizational communication and management, specifically of Equitable-PCI Trust Banking. The study was especially concerned whether formal organizational communication structure and content have an effect/s on management. Moreover, the research also delved into knowing the organizational communication climate of the said bank. The researchers used a framework based on some concepts of chaos theory. The theory basically implied the pattern of order, disorder, and the emergence of a new and better order. In the study, miscommunication was seen as a pattern of disorder. The researchers used research methods of both quantitative and qualitative natures in order to meet the objectives of the study. The survey method was used to assess the communication climate of the bank in terms of supervisor/subordinate communication, quality of information, superior openness and candor, upward communication opportunity, and reliability of information. Respondents for the survey were all officers and managers of Equitable-PCI Trust Banking. For the researchers to determine the communication policies and guidelines, frequency and purposes of formal communication activities, existence of communication supportive programs, speed and accuracy of information and instances of miscommunication, focus group discussion (FGD's) were conducted. Three focus group discussions were done. Discussants for the first two FGD's were all officers and managers of the said bank. For the third FGD, discussants were composed of the staff and/or employees of Equitable-PCI Trust Banking. These were done in order to information that would suffice for attaining the goals of the study. The data gathered from the survey were reduced to percentage and frequency tables and were described according to the variables mentioned earlier. Data gathered from the focus group discussions were sectioned according to the objectives and indicators mentioned. These were described and discussed accordingly. Although the purposes for each of the data gathering methods varied, results of the data gathered basically complemented each other. The study revealed that organizational communication has strong positive effects toward management. They were found out to have a direct kind of relationship. It was also revealed that Equitable-PCI Trust Banking has a very strict and formal organizational communication climate and structure. Furthermore, it was also shown that miscommunication contributed to better management. However, since only one organization as a unit of analysis was studied upon by the researchers, it would be beneficial for future researchers who wish to continue this study to include more organizations. If possible, to venture forth not only in organizational communication but also to other levels of communication as well. In this ligth, results of the data would be more conclusive and acceptable.